Multi-Layer Filters: Adsorption and Filtration Mechanisms for Improved Separation - Onur, Aysu; Ng, Aaron; Batchelor, Warren; Garnier, Gil (Frontiers in Chemistry, 2018)
Filters made of cellulose fibre and perlite particles were prepared using a wet laying papermaking technique. Polyamide-amine-epichlorohydrin (PAE) was added to provide wet strength. Filters were prepared at two different total basis weights of 200 and 400 grams per square metre (gsm). Single and multi-layered filters were structured for each total basis weights. The effect of total basis weights and multi-layered structure on methylene blue adsorption and silicon dioxide (SiO2) particle filtration was investigated. Methylene blue adsorption was performed in two modes: constant pressure and constant flow rate. In both operation modes, the adsorption capacity of multi-layered filters was significantly higher (16 to 100%) than for single-layer filters at the same overall weight. The effect of layer separation was also characterized using polypropylene separators and tested under constant flow rate operation. Separators provided more effective methylene blue adsorption by generating a well distributed flow. Filtration performance was quantified with 0.5 µm silicon dioxide particles under constant pressure conditions; this is to mimic bacteria rejection. Filtration capability of SiO2 particles was reduced slightly (12%) with decreasing individual filter layer thickness regardless of the multi-layered structure. Filtering polyethylene glycol (PEG) molecules with two different molecular weights was performed; however, no rejection was recorded. The filter internal pore structure was visualised by 3D-X ray computed tomography and the void fraction was quantified. 400 gsm single layer presented areas of low fibre density forming pores, while the pore volume decreased for thinner filter layers.